Echocardiographic probability of pulmonary hypertension according to the old and the new definition: a validation study. (3rd October 2022) - D'Alto, M; Di Maio, M; Romeo, E; Argiento, P; Di Vilio, A; Blasi, E; Vergara, A; Rea, G; D'Andrea, A; Golino, P; Naeije, R
Abstract: Background: According to current guidelines, the diagnosis of pulmonary hypertension (PH) relies on echocardiographic probability followed by right heart catheterization. How echocardiography predicts PH recently re-defined by a mean pulmonary artery pressure (mPAP) >20 mmHg instead of ≥25 mmHg and pulmonary vascular disease defined by a pulmonary vascular resistance (PVR) >3 or >2 Wood units has not been established. Methods: A total of 278 patients referred for PH underwent a comprehensive echocardiography followed by a right heart catheterization. Fifteen patients (5.4%) were excluded because of insufficient quality echocardiography. Results: With PH defined by a mPAP >20 mmHg, 23 patients had no PH, 146 had pre-capillary and 94 post-capillary PH. At univariate analysis, maximum velocity of tricuspid regurgitation (TRV) ≥2.9 and ≤3.4 m/s, left ventricle (LV) eccentricity index >1.1, right ventricle (RV) outflow tract (OT) notching or acceleration time <105 ms, RV-LV basal diameter >1 and PA diameter predicted PH, whereas inferior vena cava diameter and right atrial area did not. At multivariable analysis, only TRV ≥2.9 m/s independently predicted PH. Additional independent prediction of PVR >3 Wood units was offered by LV eccentricity index >1.1 and RVOT acceleration time <105 ms and/or notching, but with no improvement of optimal combination of specificity and sensibility or positive prediction. The areas under the ROC curves for different cut-off values of TRV for the prediction of mPAP >20 mmHg, mPAP ≥25 mmHg, mPAP >20 mmHg + PVR >2 Wood units and mPAP ≥25 mmHg + PVR >3 Wood units are illustrated in Figure 1A–D. Conclusions: Echocardiography as recommended in current guidelines can be used to assess the probability of re-defined PH in a referral center. However, the added value of indirect signs is modest and sufficient quality echocardiographic signals may not be recovered in some patients. Funding Acknowledgement: Type of funding sources: None.